2008
DOI: 10.1007/s12010-008-8257-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of Zinc and Iron from Steel Plant Waste using Acidithiobacillus Ferrooxidans

Abstract: The bacterial leaching of zinc and iron from solid wastes at the Isdemir iron and steel plant has been investigated using Acidithiobacillus ferrooxidans as the bacterial agent. The effects of a range of operational parameters, including particle size, solids concentration and pH, on the efficiency of the bioleaching process were investigated. In each test, several variables were determined to assess the efficiency of leaching, including slurry pH and redox potential, temperature, bacteria population and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…The results showed that the Kombucha extracts has dose-dependent wound contraction effects. Bayat et al (2009) in Iran investigated the oral Kombucha tea on cutaneous wounds mast cells in rat, and the obtained results indicated that the total mast cells count decreased in tested group on 7-15th days [43]. …”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the Kombucha extracts has dose-dependent wound contraction effects. Bayat et al (2009) in Iran investigated the oral Kombucha tea on cutaneous wounds mast cells in rat, and the obtained results indicated that the total mast cells count decreased in tested group on 7-15th days [43]. …”
Section: Discussionmentioning
confidence: 99%
“…At a 1.5% w/v initial pulp density, the bioleaching efficiency is highest because realgar is a traditional Chinese medicine that has shortcomings, including high toxicity and poor solubility. A high concentration of realgar (above 2% w/v) can inhibit the physiological activity of bacteria, leading to lower arsenic concentrations in the experimental group than in the control group [65]. At low realgar concentrations (below 0.5% w/v), the arsenic concentration under bioleaching is only slightly higher than that of the control group.…”
Section: Bioleaching Of Realgar By a Ferrooxidansmentioning
confidence: 99%
“…11. Equilibrium partial pressures of zinc vapour in Reactions (11) and (12). (11) and (12), the combination of ZnO with iron oxide phases stabilises ZnO and makes it less prone to reduction reactions.…”
Section: Zinc Removalmentioning
confidence: 99%
“…Attempts have been made by many investigators to recycle the flue dusts generated from the iron and steelmaking processes, however information on the treatment of BF and BOF dusts is limited. Processes investigated include pyrometallurgical, 1,[3][4][5][6] hydrometallurgical [7][8][9] and hybrid processes, [10][11][12] the latter involving a combination of bio-leaching, hydrometallurgical and pyrometallurgical stages. After significant effort in process development, the problem is still not well resolved.…”
Section: Introductionmentioning
confidence: 99%